Universality : a novel - Brown, Natasha (Novelist) (Random House, 2024)
"Late one night on a Yorkshire farm, in the midst of an illegal rave, a young man is nearly bludgeoned to death with a solid gold bar. An ambitious young journalist sets out to uncover the truth surrounding the attack, connecting the dots between an amoral banker landlord, an iconoclastic columnist, and a radical anarchist movement that has taken up residence on the farm. She solves the mystery, but her viral exposé raises more questions than it answers, namely: Who wrote it? Why? And how much of it is true? Through a voyeuristic lens, and with a simmering power, it focuses in on words: what we say, how we say it, and what we really mean"--